A simple method for measuring fungal metabolic quotient and comparing carbon use efficiency of different isolates: Application to Mediterranean leaf litter fungi. (4th March 2017) - Pinzari, F.; Maggi, O.; Lunghini, D.; Di Lonardo, D. P.; Persiani, A. M.
Abstract: The metabolic efficiency of different microbial groups in carbon source uses and single species storage efficiency is poorly characterised and not adequately represented in most biogeochemical models. It is proposed here a simple approach for an estimation of the metabolic quotient of fungal isolates. The method is based on the values of substrate use (respiration) and growth (biomass production) obtainable for single fungal isolates in vitro using the Phenotype MicroArray™ system to test the metabolic performance of fungi on different substrates. As a case study, this carbon-use efficiency method was used to compare a group of leaf litter fungi. The metabolic efforts of single fungal species were measured on 95 different substrates of different complexity. The respiration to biomass ratio showed a high reliability and the possibility of being used as a measurable property of the micro-organisms and an indicator of organism's performance or fitness.